SHARED LEADERSHIP SEBAGAI BAGIAN TERINTEGRITAS DALAM LEARNING ORGANISATION: BISAKAH KITA TERAPKAN? - Komariyah1, Yuyu (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
Learning organisation has been a never-ending debate among scholars to be implemented within both private and public institutions. Unlike private sectors which have been the pioneer of being learning organisation, public sector has been struggling towards its application. Many factors have obviously played a part in worsening this condition. However, there is no excuse in not trying to implement learning organisation let alone discussing it. Shared leadership as the most crucial component of putting learning organisation into reality should receive special attention in conjuction with the other aspects. Therefore, it is high time to foresee what a leader can act on initiating, supporting and developing a learning organisation.